2022
DOI: 10.3389/fnut.2022.925390
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat diet disrupts the hepatic and adipose circadian rhythms and modulates the diurnal rhythm of gut microbiota-derived short-chain fatty acids in gestational mice

Abstract: The prevalence of gestational obesity has reached epidemic proportions. Evidence supported that the interactions between the gut microbiota and circadian clocks far reached, affecting host metabolism. Our study aimed to investigate the effect of a high-fat diet (HF) on the hepatic and adipose circadian rhythms in gestational mice and to explore the role of gut microbiota-derived short-chain fatty acids (SCFAs) in mediating the effects. C57BL/6 female mice were randomly fed a standard chow diet (Ctr) or HF prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Animal studies revealed that a high-fat meal shifts the phase of circadian clock gene expression, and the underlying mechanism for this effect of a high-fat meal on circadian rhythms may be related to the FA composition of the meal, which is often summarised as the palmitic acid to oleic acid ratio (the PA/OA ratio). Other studies revealed that feeding, sleep patterns and clock oscillations in the hypothalamus and peripheral tissues were more strongly affected by meals with a high PA/OA ratio than by those with a low PA/OA ratio (1216) . In experiments with human hepatocytes, PA, a SFA, inactivated PPAR α (17) and disrupted clock gene expression (18) , while OA, a MUFA, reduced lipotoxicity caused by SFA (19) .…”
mentioning
confidence: 99%
“…Animal studies revealed that a high-fat meal shifts the phase of circadian clock gene expression, and the underlying mechanism for this effect of a high-fat meal on circadian rhythms may be related to the FA composition of the meal, which is often summarised as the palmitic acid to oleic acid ratio (the PA/OA ratio). Other studies revealed that feeding, sleep patterns and clock oscillations in the hypothalamus and peripheral tissues were more strongly affected by meals with a high PA/OA ratio than by those with a low PA/OA ratio (1216) . In experiments with human hepatocytes, PA, a SFA, inactivated PPAR α (17) and disrupted clock gene expression (18) , while OA, a MUFA, reduced lipotoxicity caused by SFA (19) .…”
mentioning
confidence: 99%
“… 19 In addition, a decrease in the relative abundance of Ruminococcus was observed in the gut following a high-fat diet; Ruminococcus is the main producer of butyrate in the body. 41 Butyrate is an SCFA that plays an active role in maintaining the overall health of the gut. 42 Furthermore, in Dal salt-sensitive rats, the abundance of Veillonellaceae was positively correlated with BP, 20 whereas Enterococci were more common in normotensive individuals.…”
Section: Different Gut Microbiota and Hypertensionmentioning
confidence: 99%
“…Dosage information:Our previous study found that 5 weeks before and throughout pregnancy HFD altered the metabolic state and gut microbiota rhythm in gestational mice. [6] Meanwhile, it is very common to build the intergenerational mice model with a maternal intervention time of 3-6 weeks before pregnancy. [16,[26][27][28] In other words, 3-6 weeks of pre-pregnancy maternal intervention could have an influence on the offspring's health.…”
Section: Maternal Intervention Of Mice Modelmentioning
confidence: 99%
“…[ 1 ] Previous studies and our recent study revealed that a high‐fat diet (HFD) contributed to behavioral and molecular circadian disruptions. [ 4–6 ] Consistently, circadian rhythms are closely associated with metabolism, as evidence suggests that circadian disruptions result in obesity and diabetes. [ 1,7 ] However, whether such circadian disruption induced by nutritional challenges is limited to the exposed generation or persists across generations remains unclear.…”
Section: Introductionmentioning
confidence: 99%